Low molecular weight multistate photoswitches based on simple norbornadiene-triazine scaffolds - Krappmann, Daniel; Müller, Adrian J.; Schulze, Erik J.; Maid, Harald; Dreuw, Andreas; Hirsch, Andreas (Angewandte Chemie. International edition, 2025)
We have synthesized and characterized a series of simple norbornadiene(NBD)-triazine architectures, including multistate photoswitches with unprecedentedly high information storage densities. The simple mono-NBDs served as suitable model systems to investigate the underlying absorption and switching characteristics. To increase the complexity stepwise, a bis-NBD derivative with a symmetric substitution pattern was investigated next. By combining different NBD substituents with varying electron demands, two asymmetric compounds, one bis-NBD and one tris-NBD, were prepared and investigated. In the case of the tris-NBD, the selective switching of the individual NBD chromophores is hampered by the too closely related optical properties of all three NBD units. On the other hand, the asymmetric photoswitch system containing two NBD-substituents fulfilled the requirements of a selectively addressable multistate system with an extremely high information storage density. Nearly all possible NBD/quadricyclane (QC) combinations could be realized here, including their reversible interconversion and the respective protonated forms. Quantum chemical calculations corroborated our experimental findings.
Version des Artikels online: July 16, 2025
Gesehen am 14.11.2025